Assessment of permeability and dry shrinkage in oil palm shell concrete enhanced by surface treatment with styrene acrylic emulsion - N. Ahmad Zamri; S. Ismail; A. Husin (Materiales de Construccion)
This article introduces oil palm shell (OPS), an agricultural waste product, as a promising substitute for traditional aggregates in concrete. OPS exhibits lightweight characteristics, reducing the overall density of structures and aligning with sustainable building practices. Despite its advantages, OPS incorporation faces challenges, particularly in terms of durability and mechanical strength. The porous nature of OPS raises concerns about its long-term performance, susceptibility to environmental factors and impact on concrete workability. To address these challenges, this article proposes a surface treatment method using styrene acrylic emulsion (SAE) to modify the physical properties of OPS. This research aims to assess the influence of different SAE coatings on the durability properties, particularly in the permeability and dry shrinkage of OPS concrete. Results show that SAE treatment enhances particle density, reduces water absorption and improves adhesion between OPS and the cement matrix, which positively impacts concrete strength.